EXPERIMENTAL APPLICATION OF IMAGE TRANSFORMATION TECHNIQUE USING MATLAB - Aashi Shrivastava,; M.P. Parsai, (EPRA International Journal of Research and Development (IJRD), 2022)
The paper elobrates the practical need todeal with image transformation, though there are multiple techniques of image transformation our work is focussed on addition of two images. The images taken in this works is of same dimensions, whereas the programming expressed in the paper will also work for images of different sizes. The work also discusses that how the effect of one image intensity can be reduced or increased so as to see the higher or lower effect on two merged images. The transformations are performed using programming code written in MATLAB.